2018
DOI: 10.1186/s12960-018-0326-4
|View full text |Cite
|
Sign up to set email alerts
|

Extent and nature of dual practice engagement among Iran medical specialists

Abstract: BackgroundDual practice (DP) by medical specialists is a widespread issue across health systems. This study aims to determine the level of DP engagement among Iran’s specialists.MethodsA pre-structured form was developed to collect the data about medical specialists worked in all 925 Iran hospitals in 2016. The forms were sent to the hospitals via medical universities in each province. The data were merged at the national level and matched using medical council ID codes, national ID codes, and eventually a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 27 publications
2
25
0
Order By: Relevance
“…We only examined GPs, while most of the other studies examined all physicians and specialists, which naturally increased the number of physicians' dual practice in other countries. In Bayat et al study, the rate of dual practice among Iranian specialists was 47.7% . Hence, for the interpretation and comparison of the results, the target groups should be the same.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…We only examined GPs, while most of the other studies examined all physicians and specialists, which naturally increased the number of physicians' dual practice in other countries. In Bayat et al study, the rate of dual practice among Iranian specialists was 47.7% . Hence, for the interpretation and comparison of the results, the target groups should be the same.…”
Section: Discussionmentioning
confidence: 95%
“…In this regard, it was found that male GPs were more inclined to work in the private sector or have dual practice in both the private and public sectors. Bayat et al indicated that female specialists in Iran were less likely to have dual practice . According to previous studies, gender was one of the most critical factors influencing physicians' economic performance, including income, working hours, and dual practice …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Analyzing interviews and documents showed significant differences between medical tariffs in public and private sectors, as well as between intra-and inter-disciplinary prices, is an important factor that led to unfavorable outcomes, that are listed below: and Six th (2016-2020) five-year Development Plan, which based on this amendment, physicians were prevented from simultaneously working in both public and private sectors (dual practice) [50,51]. In this amendment, legislators implied that the main reason for the tendency of physicians to leave the public sector or preference to work in a private sector is the financial incentive, but failed to provide practical solutions to incentivize participation in the public sector [52,53].…”
Section: Major Shortfalls and Drawbacks Brought By Implementation Of mentioning
confidence: 99%